Becoming Active Agents Through Practices of Volunteering: Immigrants’ Experiences in Rural Germany - Weidinger, Tobias (2024)
Volunteering is an important way to include immigrants at a local scale, especially in small towns and municipalities with limited arrival infrastructure. With the recent increase in immigrants, including in rural areas, volunteering practices for this target group have been much discussed, albeit with an emphasis on immigrants as vulnerable beneficiaries. There are few studies that focus on immigrants’ volunteering practices, or their function for the individual and receiving community, while empirical evidence for rural areas is explicitly lacking. In this article, we address immigrants as active agents with recourse to the concept of agency and unravel, firstly, the meanings they attribute to volunteering and reasons for their mobilisation; secondly, their access to volunteering in the German countryside; and thirdly their reflecting, practising, and sharing of agency through volunteering with an impact on themselves and their rural communities. Drawing on a qualitative, biographical‐narrative study of 72 immigrants in rural Germany, we show how cultures of volunteering—or how it is practised in different contexts—inform immigrants’ current activities, ranging from leisure practices to neighbourly help and supporting the inclusion of new arrivals. We illustrate the importance of opportunity structures and social networks for accessing volunteering and reveal individual and altruistic reasons for doing it, such as facilitating language acquisition and enhancing one’s participation, showing solidarity with immigrants, or gratitude towards the receiving society, often coinciding with expected outcomes. Volunteering allows immigrants to “perform agency” and fosters both belonging and responsibility taking for the dwelling place.